2013
DOI: 10.1111/jnc.12490
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the high‐affinity choline transporter activity and trafficking by its association with cholesterol‐rich lipid rafts

Abstract: The sodium-coupled, hemicholinium-3-sensitive, high-affinity choline transporter (CHT) is responsible for transport of choline into cholinergic nerve terminals from the synaptic cleft following acetylcholine release and hydrolysis. In this study, we address regulation of CHT function by plasma membrane cholesterol. We show for the first time that CHT is concentrated in cholesterol-rich lipid rafts in both SH-SY5Y cells and nerve terminals from mouse forebrain. Treatment of SH-SY5Y cells expressing rat CHT with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 78 publications
(189 reference statements)
2
21
0
Order By: Relevance
“…As expected, the 4 h MβCD treatment reduced membrane cholesterol to 50% of the Ctrl cells (Fig 6B). In contrast, filipin treatment did not affect membrane cholesterol (Fig 6B), which is consistent with its function to sequester membrane cholesterol without depleting it [36, 37]. Thus, MβCD treatment, which depletes cellular and membrane cholesterol, may increase MCP-1 expression and secretion and activate ERK and NF-κB by disrupting lipid raft integrity or function.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…As expected, the 4 h MβCD treatment reduced membrane cholesterol to 50% of the Ctrl cells (Fig 6B). In contrast, filipin treatment did not affect membrane cholesterol (Fig 6B), which is consistent with its function to sequester membrane cholesterol without depleting it [36, 37]. Thus, MβCD treatment, which depletes cellular and membrane cholesterol, may increase MCP-1 expression and secretion and activate ERK and NF-κB by disrupting lipid raft integrity or function.…”
Section: Resultssupporting
confidence: 69%
“…Depletion of membrane cholesterol may lead to the disruption of lipid rafts, which are the microdomains of plasma membrane enriched in cholesterol and sphingolipids, as well as caveolae, a subset of lipid raft domains consisting of structure protein caveolin [11, 35]. To determine if another cholesterol-binding reagent would also induced MCP-1 similarly to MβCD, we treated 3T3-L1 adipocytes with the polyene antibiotic filipin, which can also bind and sequester membrane cholesterol [36]. We performed a dose response experiment of filipin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments on synaptosomes or cell cultures revealed that the disruption of lipid rafts using methyl-β-cyclodextrine treatment attenuated the HACU levels through a reduction in membrane-bound CHT1 and also through altered conformation. In addition, CHT1 from cholesterol-depleted synaptosomes appeared to be more vulnerable to Aβ actions [23,61]. Since perturbation of the lipid raft integrity are involved in AD pathogenesis [62], we suppose that the attenuated effects of some AChE inhibitors on CHT1 from cholesterol-depleted synaptic membranes (indicating, e.g., their stronger requirement to CHT1 conformation) should be advantageous with regard to AD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CHT1 is specifically localized on presynaptic cholinergic nerve terminals and is directly involved in the high-affinity choline uptake (HACU) transport, a key regulatory step in the synthesis of ACh. CHT1 transporters actively transport choline from the synapsis back to the presynaptic terminals, where it is used for the de novo synthesis of ACh [18,19,20,21,22,23,24]. In contrast to AChE, however, the 3D structure of the transmembrane CHT1 is not known in details yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation